An Online Monitoring Method for Bond Wire Fatigue in IGBT Module - Hongtao Liu; Fei Wang; Xiaokang Zhang; Weiyi Xia; Lintao Ren (IEEE Journal of the Electron Devices Society)
IGBT modules are core components of power electronic converters, and their reliability has gained significant attention. Among various reliability concerns, bond wire fatigue is a prominent issue. Bond wire fatigue can alter the electrical characteristics of IGBT modules, affecting the turn-off process of the IGBT. Consequently, it leads to changes in the collector-emitter voltage spike and the auxiliary emitter-emitter voltage spike during the turn-off process. The paper proposes the utilization of the K factor parameter which is not affected by the collector current and junction temperature, based on the collector-emitter voltage spike and the auxiliary emitter-emitter voltage spike, for bond wire fatigue monitoring of IGBT modules. Additionally, the monitoring of bond wire fatigue and junction temperature of IGBT modules was achieved based on the K factor parameter and the auxiliary emitter-emitter voltage spike. This provides a basis for the reliability assessment of IGBT modules.